Remediation Strategies in Dental Education: A Scoping Review - Zakyah, Akhyar Dyni (Cakradonya Dental Journal, 2025)
While a systematic reviews of remedial interventions for medical students have been published, no such review exists for dental students. This scoping review aimed to identify the reasons, methods, and impact of remediation in dental education. Following the Arksey OMalley framework for scoping reviews, a literature search was conducted using keywords including remedial, remediation, and dental students across Google Scholar and PubMed. English-language studies published until January 2025, focusing on dental students and dental hygiene students, were included. Thematic analysis was performed on the selected articles, and from an initial yield of 1,790 articles, screening and full-text review identified 11 relevant studies. Remediation strategies varied widely, encompassing seminars and tutorials, problem-based learning, plenary discussions, lectures, web-based learning, summer courses, guided independent learning, self-reflection, individual consultations, and discrimination training. However, the available literature provides limited insight into the implementation of remedial programs in dental education. Key gaps include the comparative effectiveness of remediation methods, the influence of students factors on assessment outcomes, and remediations short- and long-term effects. Further research is needed to establish evidence-based guidelines for optimizing remediation strategies in dental education